FACTORS INFLUENCING THE USER STICKINESS OF A MOBILE NEWS APPLICATION: THE CASE OF ‘LINE TODAY APP’ - Paramartha, Putu Agya; Santoso, Harry Budi; Putra, Panca Hadi (Universitas Pendidikan Ganesha, 2021)
LINE TODAY App is a mobile news application developed by LINE Corp. The main objective of the project itself is to reach a certain amount of screen views every month which is user stickiness. But it only reached three percent of the goal in the second year of development. Due to the importance of this project to the company, the application needs an immediate and proper solution. Therefore, factors that affect the stickiness of the LINE TODAY App have to be examined. The theoretical framework of this research is constructed based on the information system success model and customer engagement theory. This study is mixed-methods research which research object is users who used LINE TODAY App. Data collection is conducted in sequence, started by collecting an online survey by involving 76 users. It was continued by conducting the contextual interview by inviting 8 interviewees. The quantitative data was processed using partial least squares structural equation modeling (PLS-SEM) using the SmartPLS application. This study found that there are four factors that affect stickiness through an intermediate variable satisfaction which are system quality, information quality, brand awareness, and enthusiasm.